ANALYSIS OF FACTORS AFFECTING THE USE OF ACCOUNTING INFORMATION IN MICRO, SMALL AND MEDIUM ENTERPRISES IN BATAM CITY - Agustin Palecha; Dian Efriyenti (Jurnal Ekonomi, 2023)
This study the creators utilized a quantitative methodology. The MSME actors in Batam City who are registered with the Batam City Cooperative and MSME Office comprise the population used in this study. Information on the quantity of MSMEs in 2022 are 282 MSMEs. Specialists utilized a non-likelihood inspecting strategy, and the testing method utilized was purposive examining. This study's sample consisted of 165 respondents, according to slovin formula calculations. The wellspring of information in this study is essential information, this information is gotten straightforwardly from, for example, appropriating surveys through the Google structure. The consequences of this study have been done by scientists who found that the main speculation shows that bookkeeping information significantly affects the utilization of bookkeeping data in MSMEs in Batam City. The subsequent speculation shows that business scale significantly affects the utilization of bookkeeping data for MSMEs in Batam City. The third speculation shows that length of business significantly affects the utilization of bookkeeping data for MSMEs in Batam City. The fourth speculation which expresses that bookkeeping information, business scale and length of business together affect the utilization of bookkeeping data on MSMEs in Batam City.